Bibliothekswissenschaft, quo vadis? : eine Disziplin zwischen Traditionen und Visionen : Programme, Modelle, Forschungsaufgaben - Hauke, Petra (K.G. Saur, 2005)
Changes in information structures and requirements demand that libraries and library science redefine their positions. They must face new challenges and present definite perspectives in the form of research goals and pilot schemes. 31 original contributions by distinguished German, American, Scandinavian, Dutch and Swiss authors shed light on the following subjects: · Library science between tradition, self-conception and public perception · Library science in the age of digital media · Library science in the service of society · Library science in the service of scientific information and communication · Library science in the service of practical librarianship · Library science in teaching, studying and profession Among the issues dealt with, are the following: electronic publishing, eLearning and information ethics, the 'Open Access' debate, conveying information competence to (not only) universities, reciprocation between the economy, politics and libraries, and finally, library science training in view of librarianship in practice. The contributions are written in either German or English, depending on the author's origins. The appendix contains abstracts in English as well as an extensive bilingual index of authors. Bibliothekswissenschaft - quo vadis? Addresses librarians, information scientists, information documentalists, academics and students of all disciplines - all who create, collect, bundle, process, mediate, or prepare for use professional information.